Lymphomatoid papulosis type A. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2017)
Lymphomatoid papulosis is a papular nodular chronic-recurrent eruption currently included in the classification of primary cutaneous T cell lymphoma, in particular CD30+ lymphomas. Recently, 251 cases of lymphomatoid papulosis in subjects under 18 years of age were reported (2). The course in children is chronic-recurrent for years, often with complete regression, but in 5,6% of cases with evolution in lymphoma (2). There are 5-6 distinct histological types of lymphomatoid papulosis, the most frequent being the classic type or type A (1), characterized by a Hodgkin-like appearance. Lymphomatoid papulosis should be differentiated from pityriasis lichenoides and anaplastic CD30 + large cell lymphoma. Pityriasis lichenoides is clinically characterized by more numerous and smaller lesions, whereas CD30+ lymphoma presents more than 2 cm large lesions that do not tend to resolve spontaneously. It is therefore essential prolonged clinical and ultrasound monitoring of these children.